Pomen prenosa vrednot med generacijami - Kežman, Mihaela (Bogoslovni vestnik, 2022)
Demographic changes that we are seeing happen have a significant influence of families. Intergenerational cooperation is no longer seen as something that we can take for granted based purely on the fact that various generations live together. Based on all of this it seems that values are losing their power. This has led us to research the area of values, in particular, we were interested in how values are being transmitted from grandparents to grandchildren through intergenerational relations. We have used a paper-pencil survey where we gathered responses from 405 respondents, aged between 65 and 75 years of age inclusive, asking them how important selected values are for their personal and how important do they see these same values for being transmitted to their grandchildren. We have found out that those values that are important for grandparents themselves are also important to be transmitted to their grandchildren. For this purpose, we have used a pre-existing questionnaire based on Musek value survey (MLV). Another interesting discovery of our research is also that the value of faith (correlation value 0,812) has proven to be the most important value for transmission to their grandchildren based on the views of grandparents. Our research also identified certain differences when it comesto the gender of grandparents and age of grandparents in relation to the transmission of values. Results of the survey can be directly used or can be used for further research purposes especially now when in times of crisis family is a value, we all must foster as necessary.
Keywords: družina; faith; family; grandchildren; grandparents; stari starši; values; vera; vnuki; vrednote